2023
DOI: 10.3390/ijms24065719
|View full text |Cite
|
Sign up to set email alerts
|

The IgSF Cell Adhesion Protein CLMP and Congenital Short Bowel Syndrome (CSBS)

Abstract: The immunoglobulin-like cell adhesion molecule CLMP is a member of the CAR family of cell adhesion proteins and is implicated in human congenital short-bowel syndrome (CSBS). CSBS is a rare but very severe disease for which no cure is currently available. In this review, we compare data from human CSBS patients and a mouse knockout model. These data indicate that CSBS is characterized by a defect in intestinal elongation during embryonic development and impaired peristalsis. The latter is driven by uncoordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Accordingly, uncoordinated calcium signaling provoked a disturbed contraction of the intestine and ureter. Notably, the level of connexin43 and connexin45 proteins, but not their mRNAs, was severely reduced in the smooth muscle layers ( Langhorst et al, 2018 ; Rathjen and Jüttner, 2023 ). Our studies on BT-IgSF described here provide an additional example of the way this subgroup of proteins plays a part in gap junction–mediated cell–cell communication.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, uncoordinated calcium signaling provoked a disturbed contraction of the intestine and ureter. Notably, the level of connexin43 and connexin45 proteins, but not their mRNAs, was severely reduced in the smooth muscle layers ( Langhorst et al, 2018 ; Rathjen and Jüttner, 2023 ). Our studies on BT-IgSF described here provide an additional example of the way this subgroup of proteins plays a part in gap junction–mediated cell–cell communication.…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s small bowel length was only 50 cm, which was consistent with a congenital short bowel. It has been reported that the early onset of clinical signs, including such as vomiting and diarrhea, in children with congenital short bowel disease suggests a poor prognosis, and delayed presentation suggests a favorable outcome ( 12 ). This patient did not develop relevant symptoms early on, and full enteral feeding was eventually successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…A congenital short small intestine is a rare developmental malformation of the small intestine that is functionally or anatomically inadequate in length, resulting in severely reduced intestinal absorptive capacity, manifesting as vomiting, diarrhea, growth retardation, and intestinal malrotation ( 10 , 11 ). Congenital short small intestine may be inherited in an autosomal recessive pattern, such as loss-of-function mutations in coxsackie and adenovirus receptor-like membrane protein, or X-linked type of inheritance ( 12 , 13 ). Currently, only two studies have reported omphaloceles in congenital short bowel syndrome ( 7 , 14 ), while most cases of short bowel syndrome are due to necrotizing enterocolitis and intestinal atresia ( 15 ).…”
Section: Introductionmentioning
confidence: 99%